Injectable Hydrogel Based on Modified Gelatin and Sodium Alginate for Soft-Tissue Adhesive - Xing, Yuhang; Qing, Xueqin; Xia, Hao; Hao, Shiqi; Zhu, Haofang; He, Yiyan; Mao, Hongli; Gu, Zhongwei (Frontiers in Chemistry, 2021)
To assist or replace the traditional suture techniques for wound closure, soft tissue adhesives with excellent adhesion strength and favorable biocompatibility are of great significance in biomedical applications. In this study, an injectable hydrogel tissue adhesive containing adipic acid dihydrazide-modified gelatin (Gel-ADH) and oxidized sodium alginate (OSA) was developed. It was found that this tissue adhesive possessed a uniform structure, appropriate swelling ratio, good injectability, excellent hemocompatibility and cytocompatibility. The adhesion capacity of the developed adhesive with optimized component and concentration was stronger than that of the commercial adhesive Porcine Fibrin Sealant Kit. All these results suggested that the developed hydrogel was a promising candidate as a soft tissue adhesive.